1992
DOI: 10.1095/biolreprod46.5.772
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor-α Stimulates the Biosynthesis of Matrix Metafloproteinases and Plasminogen Activator in Cultured Human Chorionic Cells

Abstract: To investigate the role of tumor necrosis factor-alpha (TNF alpha) in advanced collagenolysis and degradation of connective tissue components in preterm parturition, the effects of human recombinant TNF alpha (hrTNF alpha) on the production of matrix metalloproteinase 1 (MMP-1)/tissue collagenase, MMP-3/stromelysin, tissue inhibitor of metalloproteinases (TIMP), urokinase type-plasminogen activator (uPa) and prostaglandin (PG) E2 in human chorionic cells were examined in vitro. Human chorionic cells, but not a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
92
1
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(96 citation statements)
references
References 23 publications
2
92
1
1
Order By: Relevance
“…Apoptosis can also induce activation of MMPs. In addition, the same agents which have been reported to cause apoptosis in FM tissue also activate and increase transcription of MMPs, specifically, MMP-1, MMP-9 (So et al, 1992;Fortunato et al, 2002). We have reported a parallel increase in prostaglandins with induction of apoptosis in amnion epithelial, mesenchymal and WISH cells with several non-physiological (actinomycin D, cycloheximide, staurosporin) and physiological (ceramide, lactosylceramide, PGJ2 metabolites) apoptotic agents (Moore et al, 1988(Moore et al, , 1993.…”
Section: Term Fm Develops a Para-cervical "Weak Zone" Where Rupture Imentioning
confidence: 59%
“…Apoptosis can also induce activation of MMPs. In addition, the same agents which have been reported to cause apoptosis in FM tissue also activate and increase transcription of MMPs, specifically, MMP-1, MMP-9 (So et al, 1992;Fortunato et al, 2002). We have reported a parallel increase in prostaglandins with induction of apoptosis in amnion epithelial, mesenchymal and WISH cells with several non-physiological (actinomycin D, cycloheximide, staurosporin) and physiological (ceramide, lactosylceramide, PGJ2 metabolites) apoptotic agents (Moore et al, 1988(Moore et al, , 1993.…”
Section: Term Fm Develops a Para-cervical "Weak Zone" Where Rupture Imentioning
confidence: 59%
“…In non-neural cells the expression of MMPs and TIMP-1 is modulated by extracellular factors, including cytokines and growth factors like TNF-␣ (Chua and Chua, 1990;So et al, 1992), IL-1␤ (Shingu et al, 1993), bFGF, EGF, and TGF␤ (Edwards et al, 1987) and by phorbol esters . In contrast, very little is known about the regulation of TIMP-1 expression in the CNS.…”
Section: Abstract: Timp-1; Protease Inhibitor; Brain Seizures; Neuromentioning
confidence: 99%
“…Although neuronal hyperactivity may trigger early TIMP-1 upregulation in neurons, other factors, set in motion by seizures, could influence its expression in both neurons and glial cells at later time points. Among these factors proinflammatory cytokines (i.e., IL-1 ␤, TNF-␣) and bFGF, known to be induced by seizures (Minami et al, 1990;Bugra et al, 1994;Gall et al, 1994;de Bock et al, 1996) and supposedly involved in tissue repair after lesions, are efficient modulators of the expression of TIMP-1 in non-neural cells (Edwards et al, 1987;Chua and Chua, 1990;Okada et al, 1990;So et al, 1992;Shingu et al, 1993;Dayer and Burger, 1994). In addition to its most widely recognized function as inhibitor of MMPs, TIMP-1 also exhibits trophic activity (Docherty et al, 1985;Gasson et al, 1985).…”
Section: Delayed Increase Of Timp-1 In Astrocytes Of Lesioned Areasmentioning
confidence: 99%
“…This method may strengthen the quantitative performance of skin blotting, which may expand the applicability of this method as a skin assessment tool in broader fields, such as nursing and cosmetology. reported that the skin of obese people is continuously exposed to oxidative stress, collagen-degrading enzymes [15], and inflammatory cytokines, e.g., tumor necrosis factor-α (TNF-α), all of which may be linked to skin weakness [16][17][18][19][20]. In another instance, skin maceration caused by incontinence leads to incontinence-associated dermatitis, which can be prevented by assessing the reduction of skin barrier function using a simple skin assessment tool [21].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a mouse model for obesity has shown severe difficulties, involving wound healing [10,11] and the same has been equally true for human subjects [12]; obese subjects may have a higher prevalence of pressure ulcers [13] and a number of studies have reported the association between obesity and psoriasis [14]. Furthermore, it has been reported that the skin of obese people is continuously exposed to oxidative stress, collagen-degrading enzymes [15], and inflammatory cytokines, e.g., tumor necrosis factor-α (TNF-α), all of which may be linked to skin weakness [16][17][18][19][20]. In another instance, skin maceration caused by incontinence leads to incontinence-associated dermatitis, which can be prevented by assessing the reduction of skin barrier function using a simple skin assessment tool [21].…”
Section: Introductionmentioning
confidence: 99%